POLA AKTIVITAS PENGUNJUNG DALAM PEMANFAATAN RUANG TERBUKA PUBLIK TAMAN KOTA WELERI - Untiyarto, Kamdan; Arief Rahman, Ratna Ayu Permatasari (Indonesian Journal of Spatial Planning, 2025)
Weleri City Park in Weleri District, Kendal Regency, is strategically located in the city center and equipped with facilities such as a multipurpose court, a children’s playground, a jogging track, and a public transport stop. These facilities encourage the public to visit the park for a variety of activities. The study aims to map how space is used in line with visitors’ needs and preferences. A descriptive qualitative method was employed through observation and behavioral mapping, dividing the park into five zones: parking, trading, play, sports, and leisure. The findings indicate a wide range of activities, with socializing among family and friends as the most prominent, followed by sports activities that peak in the morning and late afternoon, as well as children’s play supported by the available facilities. The study concludes that the park provides physical, social, and psychological benefits as a space for relaxation, interaction, and community strengthening. However, limited facilities and cleanliness issues remain challenges, underscoring the need for improved management by local stakeholders.